Assistance for the Management of Micro, Small and Medium Enterprises (MSMEs) "Dawet Ayu" Typical of Banjarnegara - Puput Mulyono; Singgih Purnomo (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
Dawet Ayu in Banjarnegara Regency is one of the traditional culinary micro, small, and medium enterprises (MSMEs) that until now is still able to survive and continue to grow. This typical beverage product not only has cultural value, but also has the potential to be a promising economic source for the local community. However, the reality on the ground shows that Dawet Jabung's business actors are still facing various serious obstacles. Limited understanding of business management, difficulties in calculating production costs in detail, and inability to determine the right selling price of products are the main obstacles. In addition, the low knowledge related to aspects of marketing, promotion, and business communication strategies makes it difficult for this business to expand the market. As a result, some business actors have actually experienced a significant decrease in sales from year to year. To answer these challenges, community service activities are carried out through two approaches, namely Action and Quality Awareness and Rapid Rural Appraisal (RRA). Action and Quality Awareness are carried out through extensive counseling, lectures, and mentoring aimed at increasing the knowledge of business managers. In this activity, business actors are guided to understand the importance of financial recording, cost management, and strategies to improve product quality. Meanwhile, the RRA method is used to identify real needs in the field, as well as prepare training, mentoring, and coaching programs that are relevant to business conditions. The results of the activity showed an increase in the ability of partners to classify production costs into the categories of raw materials, labor, overhead, marketing, and transportation. In addition, business actors are now more skilled in determining selling prices based on the realization of costs incurred, not just estimates. They also began to compile simple bookkeeping related to assets, debts, and capital, so that business management became more professional, transparent, and sustainable